117k views
3 votes
What is the sum of StartRoot negative 2 EndRoot and StartRoot negative 18 EndRoot?

4 StartRoot 2 EndRoot
4 StartRoot 2 EndRoot i
5 StartRoot 2 EndRoot
5 StartRoot 2 EndRoot i

User Soumen
by
4.9k points

2 Answers

3 votes

Answer:

its b

Explanation:

User Tholle
by
4.5k points
1 vote

Answer:

B. 4 StartRoot 2 EndRoot i

Explanation:

Given the surd function √-2 and √-18, we are to fund the sum of both values.

Taking the sum:

= √-2 + √-18

= (√2 * √-1)+ (√18 *√-1)

from complex numbers, √-1) = i

The expression becomes

= √2 i+ √18 i

= √2 i+ √9*2 i

= √2 i+ 3√2 i

= 4 √2 i

= √-2 + √-18 = 4 √2 i

The result is 4 StartRoot 2 EndRoot i

User OKonyk
by
5.6k points